2009
DOI: 10.1186/1748-5908-4-61
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial evaluating the impact of knowledge translation and exchange strategies

Abstract: ContextSignificant resources and time are invested in the production of research knowledge. The primary objective of this randomized controlled trial was to evaluate the effectiveness of three knowledge translation and exchange strategies in the incorporation of research evidence into public health policies and programs.MethodsThis trial was conducted with a national sample of public health departments in Canada from 2004 to 2006. The three interventions, implemented over one year in 2005, included access to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
397
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(423 citation statements)
references
References 81 publications
19
397
1
6
Order By: Relevance
“…9,34,38 In addition, the language and terms used to talk about KT/E processes are often referred to as confusing, blurred and overlapping, and a lack of consensus remains on their meanings and properties. [38][39][40][41][42] A focus on language widens the discussion of these concepts beyond a simple dichotomisation of academic and non-academic understandings to encompass underlying issues of discourse and power. 43 Questions are raised regarding what is meant by 'knowledge' and who creates or owns 'it'.…”
Section: Discussionmentioning
confidence: 99%
“…9,34,38 In addition, the language and terms used to talk about KT/E processes are often referred to as confusing, blurred and overlapping, and a lack of consensus remains on their meanings and properties. [38][39][40][41][42] A focus on language widens the discussion of these concepts beyond a simple dichotomisation of academic and non-academic understandings to encompass underlying issues of discourse and power. 43 Questions are raised regarding what is meant by 'knowledge' and who creates or owns 'it'.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] We interviewed 30 guideline developers from 7 countries who said that their target users had requested GItools, but they required direction for developing GItools. 19 Existing guideline development instructional manuals lack details on how to develop GItools.…”
Section: Cmaj Openmentioning
confidence: 99%
“…Target users require support to adopt and apply guideline recommendations. [15][16][17][18] Implementation is not considered the responsibility of guideline developers but of target users. 2 Most guideline developers are already challenged by resources and time-to-issue guidelines without the additional burden of concurrently having to work with partners and stakeholders to generate GItools that support user implementation of guidelines.…”
Section: Explanation and Comparison With Other Studiesmentioning
confidence: 99%
“…Brokering is ultimately about supporting evidence-based decision-making in the organization, management, and delivery of health services" [29, p.2]. A recent randomized trial found that the utility and effectiveness of KBs will depend on the knowledge production and use context, and in some cases less costly, but still tailored, approaches to knowledge-sharing may be equally or more effective [30]. Besides type/content of knowledge, and specific user needs, contextual factors can include such things as organizational structures and communication patterns, or how the KB or other knowledge "mediator" is brought into the team or setting [31].…”
Section: Introductionmentioning
confidence: 99%